2020
DOI: 10.3390/molecules25092058
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proliferation Effect of the Newly Synthesized Valine, Tyrosine and Tryptophan–Naphthoquinones in Immortal and Tumorigenic Cervical Cell Lines

Abstract: We previously showed that microwave assisted synthesis is the best method for the synthesis of naphthoquinone amino acid and chloride-naphthoquinone amino acid derivatives by a complete evaluation of reaction conditions such as stoichiometry, bases, and pH influence. Following the same strategy, we synthesized chloride and non-chloride tyrosine, valine, and tryptophan-naphthoquinones achieving 85–95%, 80–92%, and 91–95% yields, respectively. The cyclic voltammetry profiles showed that both series of naphthoqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some PANs have been used as starting materials to prepare novel 1,4-naphthoquinone sulfonamide and sulfonate ester derivatives in good yield, as shown in Figure 5 [42]. Rivera et al, 2019, and Araujo et al, 2020, described the modification by Michael 1,4-addition, introducing several amino acids: among them are glycine, alanine, methionine, phenylalanine, asparagine, tyrosine, valine, and tryptophan in good yield (79-95%) (Figure 6) [43,44]. Some PANs have been used as starting materials to prepare novel 1,4-naphthoquinone sulfonamide and sulfonate ester derivatives in good yield, as shown in Figure 5 [42].…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some PANs have been used as starting materials to prepare novel 1,4-naphthoquinone sulfonamide and sulfonate ester derivatives in good yield, as shown in Figure 5 [42]. Rivera et al, 2019, and Araujo et al, 2020, described the modification by Michael 1,4-addition, introducing several amino acids: among them are glycine, alanine, methionine, phenylalanine, asparagine, tyrosine, valine, and tryptophan in good yield (79-95%) (Figure 6) [43,44]. Some PANs have been used as starting materials to prepare novel 1,4-naphthoquinone sulfonamide and sulfonate ester derivatives in good yield, as shown in Figure 5 [42].…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
“…Lawsone Mannich bases are 2-hydroxy-3-(aminomethyl)-1,4-naphthoquinone compounds with important biological activities such as antiparasitic, antibacterial, anticancer, and antiviral, which have a particular interest in medicinal chemistry because the Mannich reaction forms a C-C bond with nitrogencontaining derivatives. This section presents molecules with promissory activity, as shown in Table 1 [31,[42][43][44][45][90][91][92]. showed MICs of 49.7 µ g mL −1 against S. aureus and 24.7 µ g mL −1 against E. coli by 63*.…”
Section: Biological Evaluations Of Nitrogen Nq Derivativesmentioning
confidence: 99%
“…Further studies have shown that hydrophobic and aromatic amino acids have better inhibitory effects on cell proliferation. 190…”
Section: Quinone-indole Derivativesmentioning
confidence: 99%
“…Further studies have shown that hydrophobic and aromatic amino acids have better inhibitory effects on cell proliferation. 190 Shikonin is a natural product of 1,4-naphthoquinones, derived from the roots of Lithospermum species and has antitumor 191 and anti-viral activities. 192 Researchers designed and synthesized a series of shikonin derivatives, and evaluated the antitumor activity and antiviral activity of these derivatives.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…An important natural compound found in plants is naphthoquinones (NQ), where 1,4-carbonyl position and hydroxyl groups in the naphthalene ring is frequent. NQ are privileged in design and drug discovery due to their structural properties and biological actions such as antibacterial [7,8], antifungal [9,10], anticancer [11][12][13], antimalarial [14], and antiviral [15]. In most cases, the biological action is related to redox and acid properties, which can be modulated by adding different atoms or groups to NQ [16].…”
Section: Introductionmentioning
confidence: 99%